A local excitation and measurement approach for decentralized damage detection using transmissibility functions. Issue 3 (20th August 2015) - Zhu, Dapeng; Yi, Xiaohua; Wang, Yang
Summary: In order to assess structural safety conditions, many vibration‐based damage detection methods have been developed in recent years. Among these methods, transmissibility function analysis can offer advantages in easy and low‐cost implementation, as well as independency to the magnitude and waveform of an excitation record. Harnessing these features, a decentralized structural damage detection procedure is proposed in this paper. The proposed procedure only requires measurements in one small area at a time, and thus, is ideal for using limited number of sensors upon a large‐scale structure. This study also investigates the nature of transmissibility functions for damage detection in an analytical manner, based on a chain‐like spring–mass–damper system with multiple degrees‐of‐freedom. The analytical derivation is validated through numerical simulation and laboratory experiments using mobile sensors. Copyright © 2015 John Wiley & Sons, Ltd.